2009
DOI: 10.1086/606166
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Risk Stratification Model for Surgical Site Infection after Abdominal Hysterectomy

Abstract: Objective The incidence of surgical site infection (SSI) ranges widely from 2-21% after hysterectomy. There is insufficient understanding of risk factors to build a specific risk stratification index. Methods Retrospective case-control study of 545 abdominal and 275 vaginal hysterectomies from 7/1/03 - 6/30/05 at four institutions. SSIs were defined using CDC/NNIS criteria. Independent risk factors for abdominal hysterectomy were identified by logistic regression. Results There were 13 deep incisional, 53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 32 publications
3
60
0
8
Order By: Relevance
“…The study showed that obesity was a strong risk factor for postoperative complications even in a fast track setting. This agrees with results from other studies of benign abdominal hysterectomy 3,4,6,19 . Contrary to the finding presented by Brummer et al 3 we found that previous laparotomy was strongly associated with an increased risk of complications.…”
Section: Discussionsupporting
confidence: 92%
“…The study showed that obesity was a strong risk factor for postoperative complications even in a fast track setting. This agrees with results from other studies of benign abdominal hysterectomy 3,4,6,19 . Contrary to the finding presented by Brummer et al 3 we found that previous laparotomy was strongly associated with an increased risk of complications.…”
Section: Discussionsupporting
confidence: 92%
“…Other independent risk factors in our cohort were morbid obesity (BMI > 40), advanced age ( > 75 y), and dirty or contaminated wound classes, which are similar to risk factors reported by others [14][15][16]. In these studies, blood transfusion, diabetes mellitus, and smoking have also been identified as risk factors for SSI after hysterectomy.…”
Section: Discussionsupporting
confidence: 88%
“…Morbid obesity and elevated ASA class are widely considered risk factors for complications of surgery [10][11][12]. Thus, ASA class ‡ 3 was an independent risk factor for SSI.…”
Section: Discussionmentioning
confidence: 99%